ANNA DOBROVOLSKAIA: The Development of Jury Service in Japan. A square block in a round hole - Watson, Andrew R. J. (Zeitschrift für Japanisches Recht, 2017)
Routledge, London / New York 2017, 283 pp., £ 95; ISBN: 978‑1‑4724‑8255‑6